A imagem como brinquedo: a relação entre crianças e desenhos animados à luz da divisão de gênero - Ponte Filho, Marcus Henrique Linhares (2010)
Cartoons always represented a great thematic focus for children’s entertainment and therefore enjoy popularity among this public. However, despite having a privileged status among children, cartoons are still seen with distrust by teachers and parents. This essay investigated how is the relationship between children in scholar age and their favorite cartoons, giving special attention to the genre division presented in these programs that influences the relationship between boys and girls about what they watch. The research, in an ethnographic mold, was realized with children of 2nd year elementary school, in two schools of the city (a private one, and a public one). In all, were observed four classes of 2nd year elementary school, and could be seen that there’s a clear delimitation between male playful culture and female playful culture, in the mood of they are presented in cartoons. Although, this delimitation between male and female presented in television cartoons, is not a rigid rule, and the research tried to understand what children think about cartoons they watch on TV, and how is the genre differentiation in the choice of these programs